Root Canal Renaissance- A Comparative Evaluation of Herbal Extracts as Alternative Irrigants in Eradicating Enterococcus Faecalis: An in Vitro Study - Dr. Tanu Tewari, Dr. Pranjal Jain, Dr. Vishesh Gupta, Dr. Megna Chauhan, Dr. Gunja Verma, Pro.(Dr.) Praveen Singh Samant (Journal of Daoist Studies, 2026)
Introduction: Irrigation and disinfection of root canals plays a very important role in the success of a root canal treatment as the root canal system anatomy is extremely complex and diverse and it is not always possible to clean and shape it effectively. Aim: The aim of this study was to evaluate and compare the antimicrobial efficacy of chlorhexidine, neem leaf extract, lemon peel extract and combination of neem leaf extract & lemon peel extract against Enterococcus faecalis. Method: The microorganisms selected for this study is Enterococcus faecalis (ATCC 29212). The culture was grown overnight in Brain Heart Infusion Broth at 37 degree Celsius on a rotary shaker at 150 revolutions per minute, with bacterial growth monitored by changes in turbidity at 24 hours. Spread plate method was used to determine the bacterial count in CFU at different time intervals. After confirming the growth of the respective microorganisms in the broth, paper points were dipped in test tube containing test microorganism and then transferred to test tube containing test irrigants for stipulated time and then incubated for 48 hrs. After incubation broth of each test tube was spread on nutrient agar plate of 10-6 dilution. NAM plates were then inverted for bacterial count. Results Chlorhexidine showed maximum antimicrobial activity against E. faecalis, followed by Neem leaf extract, Lemon peel extract and lastly mixture of Neem leaf and Lemon peel extract, difference being statistically significant. Conclusion: CHX exhibited the most potent antibacterial activity, on other hand, among the tested herbal agents, Neem leaf extract showed comparable efficacy at prolonged exposure times, suggesting its potential as an alternative root canal irrigant. Lemon peel extract also displayed antimicrobial properties, though its effectiveness was lower compared to CHX and Neem leaf extract.